2006
DOI: 10.1111/j.1574-695x.2006.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

T-h-2 immunity and CD3+CD45RBlow-activated T cells in mice immunized with recombinant bacillus Calmette–Guérin expressing HIV-1 principal neutralizing determinant epitope

Abstract: The genetic engineering of Mycobacterium bovis-bacillus Calmette-Guérin to express foreign epitopes is an attractive strategy in the field of epitope vaccines. We constructed an 'epitope-trap vector' with Mycobacterium tuberculosis chaperonin-10 as a carrier antigen and used it to express the HIV-1 principal neutralizing determinant epitope. We also identified a new chaperonin-10 promoter that was hyperexpressive compared with the heat shock protein-65 promoter. Splenocytes from recombinant bacillus Calmette-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…A comparative analysis of the groE promoter with the groEL2 promoter showed that, the former was much more active than the latter both in E. coli and in M. smegmatis (Fig. 1) in accordance with our previous observation (Aravindhan et al , 2006). It is of interest to note that the groE promoter contains one CIRCE element, while the groEL2 promoter contains two such sequences and might be under tight repression (Stewart et al , 2002a, b).…”
Section: Resultssupporting
confidence: 92%
“…A comparative analysis of the groE promoter with the groEL2 promoter showed that, the former was much more active than the latter both in E. coli and in M. smegmatis (Fig. 1) in accordance with our previous observation (Aravindhan et al , 2006). It is of interest to note that the groE promoter contains one CIRCE element, while the groEL2 promoter contains two such sequences and might be under tight repression (Stewart et al , 2002a, b).…”
Section: Resultssupporting
confidence: 92%
“…T-cell activation also leads to CD45RB regulation, an essential marker that determines the fate of T cells from naive to effector/memory cells. The generation of effector T cells that will undergo development to memory cells is an essential correlate of protection in determining the efficacy of vaccines ( 33 , 34 ). All effector subsets evaluated, i.e., effector CD4 and effector CD8, were increased in the BpOmpW-immunized group, indicating that the antigen produces a robust effector recall response that is likely to lead to a memory response, a hallmark of an efficacious vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…T cell activation also leads to CD45RB regulation, an essential marker that determines the fate of T cells from naïve to memory cells. The generation of effector T cells that will undergo development to memory cells is an essential correlate of protection in determining the efficacy of vaccines (Robinson & Amara, 2005;Aravindhan et al, 2006). All effector subsets evaluated, i.e., effector CD4 and effectors CD8 were increased in BpOmpW immunized group, indicating that the antigen produces a robust effector recall response that is likely to lead to a memory response, a hallmark of an efficacious vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…All rights reserved. No reuse allowed without permission.undergo development to memory cells is an essential correlate of protection in determining the efficacy of vaccines(Robinson & Amara, 2005;Aravindhan et al, 2006). All effector subsets evaluated, i.e., effector CD4 and effectors CD8 were increased in BpOmpW immunized group, indicating that the antigen produces a robust effector recall response that is likely to lead to a memory response, a hallmark of an efficacious vaccine.The early immune responses to control melioidosis infection are predominantly mediated by IFN-g in both CD4 + and CD8 + T cells, and as recently reported in NK and DN cells(Kronsteiner et al, 2019; Rongard et al, 2020).…”
mentioning
confidence: 99%